2017
DOI: 10.1080/13562517.2017.1391201
|View full text |Cite
|
Sign up to set email alerts
|

Articulating identities and analyzing belonging: a multistep intervention that affirms and informs a diversity of students

Abstract: This article describes a multistep intervention developed for an undergraduate course called 'Advocating Diversity in Higher Education.' The goal of the intervention was to affirm diversity and foster a sense of inclusion among students within and beyond the course. We contextualize the intervention in student protests during 2015 and 2016 regarding racial and other forms of discrimination on college and university campuses in the United States, and we describe how it is informed by several theoretical frames … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 22 publications
1
16
0
1
Order By: Relevance
“…For participants, curriculum co-creation means working together towards shared aims, feeling that ‘we are all in this together’ (Staff 8) and that ‘it’s not them and us, it’s just us ’ (Staff 4). The process-focused, relational dimension of staff and student collaboration in sharing decision-making is important here, and it is prevalent in the literature that notes the sense of community and belonging that develops during curriculum co-creation (Blau & Shamir-Inbal, 2018 ; Bovill, 2020b ; Cook-Sather et al, 2018a ; Kaur et al, 2019 ; Lubicz-Nawrocka, 2019a ; Masika & Jones, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For participants, curriculum co-creation means working together towards shared aims, feeling that ‘we are all in this together’ (Staff 8) and that ‘it’s not them and us, it’s just us ’ (Staff 4). The process-focused, relational dimension of staff and student collaboration in sharing decision-making is important here, and it is prevalent in the literature that notes the sense of community and belonging that develops during curriculum co-creation (Blau & Shamir-Inbal, 2018 ; Bovill, 2020b ; Cook-Sather et al, 2018a ; Kaur et al, 2019 ; Lubicz-Nawrocka, 2019a ; Masika & Jones, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…These authors also describe the important values of respect, reciprocity and shared responsibility. Although both partnership and co-creation initiatives often seek to include diverse student voices whilst enhancing learning and teaching (Cook-Sather et al, 2018a ; Lubicz-Nawrocka, 2019a ), many partnership examples involve small numbers of already highly engaged students in optional projects in contrast to whole-class co-creation initiatives that are embedded into coursework (Bovill, 2020b ). Bovill ( 2020a ) suggested that co-creation and partnership often overlap in their emphasis on democratic values and shared decision-making, although partnership can imply a level of equality that some staff find hard to align with the reality of academic structures and constraints.…”
Section: Existing Definitions Of Curriculum Co-creationmentioning
confidence: 99%
“…Since the advent of the program, Alison has supported over 230 faculty members and 145 student consultants in a total of more than 280 partnerships. She has also engaged in partnership with students in course design and facilitation (Cook-Sather, Des-Ogugua, & Bahti, 2017). Anita has worked as a student partner since 2015, collaborating with four different faculty partners and co-facilitating partnership forums.…”
Section: Contextmentioning
confidence: 99%
“…In particular, we explore the experiences of students who have participated in pedagogical partnership programs, and who identify as members of equity-seeking groups (groups that experience social marginalization, oppression, and inequity). We ask how such students perceive the capacity of partnership programs to support equity and inclusion in the classroom, and thereby contribute to the growing body of literature considering the intersections between partnership and equity (Colón García, 2017;Cook-Sather, 2018;Cook-Sather et al, 2018;Cook-Sather & Agu, 2013;de Bie et al, 2019).…”
mentioning
confidence: 99%